(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
In the Argentinean littoral zone several trans- gressive - regressive events took place during the Quaternary. Excellent examples of these events are recorded in the Bahía Samborombón coastal area in northeastern Buenos Aires province (Fig. 1). Following the stratigraphic scheme of Fidalgo et al. (1973) modified by Fucks et al. (2010), deposits of the Canal de las Escobas Formation (Holocene) were analyzed (Figs. 2, 3). The Canal de las Escobas Formation was discriminated into 4 members (Fucks et al., 2010), the Destacamento Río Salado Member (tidal flat, 5.8-7 ka B.P.), the Cerro de la Gloria Member (beach ridge, ca. 3-8 ka B.P.), the Canal 18 Member (coastal plain, 6-7 ka B.P.) and the Canal 15 Member (coastal plain, 3 ka B.P. to present). Fourteen detailed sedimentary sections were logged in the study area (Fig. 4), taking into account lithology, primary sedimentary structures, geometries of the sedimentary bodies with their orientation and the hierarchy of the bounding surfaces, as well as the palaeontological (predominantly molluscan) content. Thirteen sedimentary facies were defined (Figs. 5, 6) which were grouped into three major divisions: siliciclastic sandstones, fine-grained sili- ciclastic and carbonatic bioclastic rocks. The excellent preservation of the Canal de las Escobas Formation in the study area allowed the recognition of five sedimentary units based on the spatial facies arrangement and the hierarchy of internal surfaces. These units are: sand and bioclastic ridge, washover, lagoon and coastal plain units (Figs. 7, 8, 9, 10, 11). In order to determine the palaeoenvironmental evolution, based on the stacking patterns of the sedimentary units together with the hierarchy of the sedimentary discontinuity surfaces, six stages were devised after the maximum Holocene transgression (Fig. 12). Stages 1 and 2 correspond to the development of a sand ridge as a response to the erosion and reworking of a previous spit system (Fig. 3; Facies Pinamar). Subsequently, during stages 3 to 5, a bioclastic ridge was amalgamated with the sand ridge (Fig. 12). Simultaneously to these five stages, in a landward position, lagoon and washover deposits were developed (Fig. 12). Finally, during stage 6 the continuous sea level fall generated the actual coastal plain deposits (Fig. 12). The sudden change in the ridge deposits composition, from sandy sediments to almost exclusively bioclastic (carbonate) between stages 2 and 3 can be interpreted as the combined result of an increase in carbonate productivity along with a decrease of siliciclastic supply together the coast. This stage would have been developed approximately 5-6 ka B.P. (Marine Isotope Stage, MIS, 1), in coincidence with the Holocene Climatic Optimum or Mid-Holocene Thermal Maximum (sensu Briner et al., 2006) during which the very special climatic conditions may have led to the proliferation of large communities of benthic organisms, particularly bivalve mollusks, which are not so abundant today. The high occurrence of Mactra isabelleana in the beach ridges of Bahía Samborombón, including all dimensions and ontogenetic stages and excellent preservation of the shells, indicates that this bivalve represents an autochthonous element of the coastal native communities, suggesting high adaptive radiation of this species in the area and time span considered, when atmospheric-oceanic circulation patterns / changes in the prevalent shallow oceanic currents are documented by different sources of evidence (palaeobiodiversity, palaeobiogeography, stable isotopes) and the warm Brazilian current (mo- ving southwards) prevailed over the cold Malvinas current (flowing northwards) (Fig. 3). This change in the intensities of the ocean currents would have originated a dual effect: firstly, a greater contribution of warm-temperature waters to the bay and secondly, the change in the terrigenous input. The contribution of sand, due to erosion and reworking of the previous spit facies, would have drastically decreased, whereas the contribution of terrigenous may have been restricted from the north coming from the Río de la Plata (Fig. 3). Nevertheless, no changes in composition and/or texture were observed in siliciclastic material between the sand and bioclastic ridges units. This would be related to the sort of material transported by the Río de la Plata, which is mostly pelitic and potentially washed by tidal activity as it is well documented for similar Quaternary deposits from other areas (Meldahl, 1995). Considering the whole dataset gathered, we pro- pose an alternative sequence stratigraphic scheme for the Holocene ridge development from Bahía Samborombón (Fig. 13). This ridge is now considered originated as a consequence of a forced regression (ie. part of a falling stage system tract) instead of the previously interpretation during the late stage of sea level rise (ie. part of a highstand system tract). Both eustatic and climatic controls can be recognized, although with different orders of magnitude, which controlled the genesis of the studied deposits. In turn, this study provides an example of the strong changes occurred in coastal environments as a result of climate change, particu- larly in the context of global warming episodes which characterized interglacial periods of the Quaternary in South America (e.g. MIS 1, 5, 11).